Greenhouse gases emissions from the logistics sector: the case of Hong Kong, China. (15th September 2015) - To, W.M.
Abstract: In this study, greenhouse gases (GHG) emissions from the logistics sector were investigated using Hong Kong as an example. The data including cargo freight between Hong Kong and other places by different transport modes (i.e. aircraft, container ships, trucks, and trains) for the period of 2007–2012 were collected. Combining transport data with the GHG emitted from each mode of transport in terms of tonne CO2 -eq per kilotonne-kilometer, GHG emissions for each transport mode and the total amount of GHG emissions were determined. In 2012, the total cargo freight between Hong Kong and other places via air freight was 4024 kilotonnes and produced 22, 623 kilotonnes of CO2 -eq. The total cargo freight via sea freight was 269, 283 kilotonnes and produced 12, 784 kilotonnes of CO2 -eq. The total cargo freight via land freight was 26, 215 kilotonnes and produced 463 kilotonnes of CO2 -eq. The total amount of GHG emissions was 35, 834 kilotonnes of CO2 -eq. The environmental effectiveness of Hong Kong's logistics sector was obtained by normalizing the total amount of GHG emissions with respect to the value added. The calculated value was 534 tonnes of CO2 -eq per million HKD value added. The results of scenario analysis showed that the amount of GHG emissions could be reduced at about 100 kilotonnes of CO2 -eq. per 100 kilotonnes of cargo by switching a portion of air cargo movements to and from mainland China to land freight or sea freight. Highlights: Air, sea, road and rail freight transport services produce greenhouse gases. The total cargo throughput via Hong Kong was 299, 522 kilotonnes in 2012. GHG emission amounted to 35, 834 kilotonnes of CO2 -eq. due to freight services. Air freight produces the most GHG while rail freight produces the least GHG.